Small molecules and targeted therapies in distant metastatic disease - Hersey, P. (Oxford University Press, 2009)
Chemotherapy, biological agents or combinations of both have had little impact on survival of patients with metastatic melanoma. Advances in understanding the genetic changes associated with the development of melanoma resulted in availability of promising new agents that inhibit specific proteins up-regulated in signal cell pathways or inhibit anti-apoptotic proteins. Sorafenib, a multikinase inhibitor of the RAF/RAS/MEK pathway, elesclomol (STA-4783) and oblimersen (G3139), an antisense oligonucleotide targeting anti-apoptotic BCl-2, are in phase III clinical studies in combination with chemotherapy. Agents targeting mutant B-Raf (RAF265 and PLX4032), MEK (PD0325901, AZD6244), heat-shock protein 90 (tanespimycin), mTOR (everolimus, deforolimus, temsirolimus) and VEGFR (axitinib) showed some promise in earlier stages of clinical development. Receptor tyrosine-kinase inhibitors (imatinib, dasatinib, sunitinib) may have a role in treatment of patients with melanoma harbouring c-Kit mutations. Although often studied as single agents with disappointing results, new targeted drugs should be more thoroughly evaluated in combination therapies. The future of rational use of new targeted agents also depends on successful application of analytical techniques enabling molecular profiling of patients and leading to selection of likely therapy responders.